Estudo de painéis sanduíches de poliéster reforçado com fibras vegetais para aplicação como forro - Ferreira, Monise Ramos da Silva (2013)
The purpose of the work is to produce and characterize mechanically sandwich panels to using as ceiling in buildings. The faces of the panels were made of composites reinforced by ramie and sponge gourd fibers, and the cores were made of sponge gourd and expanded polystyrene-EPS. The faces of the sandwich panels were produced with different fiber contents, characterized for tensile mechanical properties and numerically simulated. The EPS and sponge gourd were studied as core materials. The flexural mechanical performance of the panels was tested experimentally and simulated by Finite Element Method. The numerical simulation was also used as tool for qualitative analyzes in the pre-design of the panel components considering variation of materials, fiber contents and thickness of faces and cores. The faces of the sandwich panels were manufactured with composite of polyester reinforced by ramie bidirectional cloth, and combined with the cores of EPS and sponge gourd. The results show the manufactured sandwich panels are feasible for use as ceiling.